Intrauterine Contraceptive Device Translocation Leading to Right Anteromedial Ovarian Surface Impingement and Laparoscopic Retrieval: A Case Report and Literature Review - Adeel Anwaar; Riyan Imtiaz Karamat; Mikail Khanzada; Aymar Akilimali; Minahil Aamir; Mirza Ammar Arshad; Ihtisham Haider Bhatti; Saad Rashid; Taimur Sulaiman Kayani; Sadia Ansar; Shifa Batool; Abdullah Saif Khan; et al. (Clinical Case Reports)
ABSTRACT We report a rare case of a 29‐year old woman presenting with abdominal pain, whose initial examination failed to identify intrauterine contraceptive device (IUCD) threads. IUCD migration was confirmed by CT scan and subsequent single‐port laparoscopic retrieval alleviated her symptoms.